Higher education expansion and individual health improvement: concurrent discussion of the blocking effect on the intergenerational transmission of health - Yifei Chu; Sirui Chen; Lixia Zhang (Frontiers in Public Health, 2025)
BackgroundThe relationship between higher education and individual health is important for improving regional human capital for health. Considering the differences in education system development and health infrastructure between China and developed countries, it is necessary to explore the specific impact of higher education expansion on individual health in China.MethodsThis study employs the cohort DID approach to examine how higher education expansion affects individual health, with a particular focus on its role in disrupting the intergenerational transmission of health, drawing data from the China Education Statistical Yearbook and the China Health and Retirement Longitudinal Study (CHARLS).ResultsResults show that higher education expansion promotes individual health improvements by enhancing academic qualifications and access to better employment opportunities, with urban dwellers, women and individuals from well-educated families receiving more benefits. Higher education expansion disrupts the intergenerational transmission of health, and younger individuals exposed to new academic and social environments tend to develop health-related beliefs and behaviors that differ from their family influences.ConclusionThis study provides insight into the social benefits of higher education, and furthermore offers a new perspective on addressing long-standing health inequalities.